2013
DOI: 10.1002/jor.22521
|View full text |Cite
|
Sign up to set email alerts
|

In vivo diagnostics of human knee cartilage lesions using delayed CBCT arthrography

Abstract: The aim of this study was to investigate the feasibility of delayed cone beam (CBCT) arthrography for clinical diagnostics of knee cartilage lesions. Knee joints with cartilage lesions were imaged using native radiography, MRI, and delayed CBCT arthrography techniques in vivo. The joints were imaged three times with CBCT, just before, immediately after (arthrography) and 45 min after the intra-articular injection of contrast agent. The arthrographic images enabled sensitive detection of the cartilage lesions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 40 publications
1
61
1
Order By: Relevance
“…1c). Similarly as in a previous study17, a delayed image was acquired at 45 min after the injection of contrast agent. Here, due to lower concentration of contrast agent, the delayed image was utilized in the approximation of volumetric bone mineral densities (vBMDs) in order to minimize errors caused by beam hardening artefact often present in CBCT images.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1c). Similarly as in a previous study17, a delayed image was acquired at 45 min after the injection of contrast agent. Here, due to lower concentration of contrast agent, the delayed image was utilized in the approximation of volumetric bone mineral densities (vBMDs) in order to minimize errors caused by beam hardening artefact often present in CBCT images.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to segmentation of the damaged tissue, a mask representing completely healthy tissue was created by manually interpolating the intact tissue surface over the defect. Other tissue areas were segmented manually or by using a combination of thresholding and morphological operations17.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline ultrasound detected gray-scale synovitis and power Doppler signals predicted radiographic progression of hand OA after 5 years 62 . Another study showed that ultrasound detected inflammatory features, including synovial thickening, effusion and power Doppler signal, especially when persistently 3 Radiography Hip and pelvic geometry are associated with the risk of compartment-specific knee OA Thomas GE, et al 49 Radiography Cam-type FAI and acetabular dysplasia predict development of hip OA and joint replacement High bone mineral density is associated with knee and hip OA Hardcastle SA, et al 4e6 Radiography High BMD Z scores are associated with increased prevalence of hip and knee OA, specifically osteophytosis Potential new approaches to examining joint structures Turunen M, et al 7 CT CBCT can measure volumetric BMD of cortical, trabecular, and subchondral trabecular bone Kokkonen HT, et al 8 CT Arthrographic images enables sensitive detection of cartilage lesions Riecke BF, et al 10 US Ultrasound score is reliable and valid in detecting knee OA Abraham AM, et al 14 US US demonstrates higher prevalence of osteophytes in hand and hip OA than radiographic studies Liukkonen J, et al 15 US Arthroscopic ultrasound imaging quantitatively evaluates articular cartilage Hirata Y, et al 16 Kobayashi N, et al 17 PET 18F-fluoride uptake is associated with mechanical stress in hip OA and can detect bone abnormalities earlier than MRI Ultrasonographic abnormalities correlate with clinical endpoints Hall M, et al 11 US Effusion and synovial hypertrophy are more common in knee OA, with severity correlating with radiographic severity of knee OA Birn J, et al 12 US Large joint effusions correlates with rapidly destructive hip OA Malas FU, et al 13 US Meniscal bulging is associated with radiographic joint space narrowing and KL grades What is new in magnetic resonance imaging? Morphological structural abnormalities predict clinical endpoints Sharma L, et al 19 MRI Cartilage damage, BMLs, meniscal tears, and meniscal extrusion are associated with prevalent frequent knee symptoms and/or incident persistent symptoms Roemer FW, et al 21 MRI Cartilage damage, BMLs, meniscal damage, synovitis and effusion predicted short-term need for knee joint replacement Eckstein F, et al 22 MRI Accelerated cartilage thickness loss is greatest closest to the time of knee replacement Composition of cartilage influences morphometry Crema MD, et al 25 MRI Poorer dermis endpoints are associated with increased cartilage thickness, potentially representing "cartilage swelling" Ukiah T, et al 26 MRI Diffusion tensor imaging can distinguish early cartilage damage Wyatt C, et al …”
Section: Mri and Ultrasound Findings Predict Progression Of Hand Oa Amentioning
confidence: 99%
“…Arthrographic images enabled sensitive detection of cartilage lesions. The contrast agent partition in intact cartilage (International Cartilage Repair Society, ICRS, grade 0) was lower than that of cartilage surrounding the ICRS grade IeIV lesions 8 . Another study used contrast enhanced CBCT to image contrast agent diffusion in isolated human menisci and found that shorter delay between injection and imaging (e.g., 40 min) could be feasible in clinical diagnostics of meniscal pathologies 9 .…”
Section: New Lessons From Ctmentioning
confidence: 99%